Inequality of opportunities of educational achievement in Turkey over time - Aysıt Tansel (Turkish Economic Association, 2015)
This study investigates inequality of opportunity in educational achievements in Turkey over time. For this purpose we use test scores of PISA in mathematics, science and reading achievement of 15-year-olds over the period 2003-2012. Since the different waves of the PISA test cover only a fraction of the cohorts of 15-year olds we take into account the inequality of opportunity in access to the PISA test as well as the inequality of opportunity of the academic achievement in the PISA test. This procedure enables a proper over time comparison. We estimate the effect of circumstances children are born into on their academic achievement as evidenced in their PISA test scores. The main findings are as follows. First, confirming the previous studies we find that inequality of opportunity is a large part of the inequality of educational achievement in Turkey. Second, the inequality of opportunity in educational achievement shows a slightly decreasing trend over time in Turkey. Third, the inequality of opportunity figures based on the mathematics, science and reading achievements exhibited similar trend over time. Forth, the family background variables are the most important determinants of the inequality in educational achievement which is a consistent pattern over time. However, there is also evidence of slight weakening of these factors over time. Policies are necessary to improve equality of opportunity in education in Turkey.
Keywords: I24; D63; 330; FDI; Inequality of opportunity; Education; Turkey